Affective Commitment as a Mediator of the Influence of Work Culture and Training on Employee Performance - Restian, Yhoni; Satoto, Eko Budi; Sanosra, Abadi; Qomariah, Nurul (Budapest International Research and Critics University, 2024)
The purpose of this study was to determine the impact of work culture, training on affective commitment and employee performance at the Population and Civil Registration Office of Jember Regency. This study used a census method sample, with respondents from 103 employees. Using a questionnaire to collect data and quantitative techniques such as instrument testing, and hypothesis testing to analyze data. The amount of p-value is obtained from the output on WarpPLS 07, then the direct and indirect effects of the relationship between the variables can be known. The results of the study indicate that work culture has a positive and significant effect on affective commitment. Training has a positive impact on affective commitment. Work culture affects employee performance. Training carried out by the organization has an impact on employee performance. Finally, affective commitment has an impact on employee performance.